Craniopharyngioma in adults: a case report - Dhanju, Avtar Singh; Narang, Nisha; Kaur, Manavdeep; Rikhye, Rishabh; Jassal, Pankaj; Singh, Adab Alwinder (International Journal of Advances in Medicine, 2023)
We are discussing a case report of 70-year-old male patient with craniopharyngioma who presented with complaint of high grade fever and altered sensorium with presence of meningeal irritation signs and papilledema in fundus examination. MRI 3D brain showed elongated lobulated mass lesion in the suprasellar region. It mostly occurs in young age before 20 years of age with features of headache, projectile vomiting and signs of raised intracranial pressure but there is possibility of its occurrence in older age group. It arises from embryologic squamous epithelial remnants of the craniopharyngeal duct or Rathke’s pouch. It develops near the hypothalamus near the pituitary gland that controls growth and many body functions. Usually, they are benign but can be malignant sometimes as they can cause serious problems by interfering with neuroendocrine structures or neuropsychological complications. There are only few cases of craniopharyngioma in old age patients worldwide.